Identificación de especies arbóreas y arbustivas para la elaboración de una propuesta de un plan de manejo en zonas de alta vulnerabilidad física y ambiental en el sector la esperanza (transecto 7), de la parroquia El Tingo, cantón Pujilí, provincia de Cotopaxi - Basantes Bastidas, Zaida Marilú (2015)
The present research work reflects the current state of the floristic composition of the native forest La Esperanza, and it provides data related to the density, abundance, dominance and use value of identified species. In the study area (Transect N ° 7) 24 species were inventoried belonging to 17 families, of which registered species as native in this study are the following: Tripliaris cumingiana (Férnan Sanchez) LC; balsa (Ochroma pyramidalis); laurel (Cordia alliodora) VU; Pambil (Iriartea deltoida) LC; dragon's blood (Croton urucurana), the same as the Red Book is considered to be vulnerable for the deforestation and the burning of forest to change land use in these areas, and Canelo species registered as endemic: rough Octea (Lauraceae ) (CR), is critically endangered.